An innovative shear links as dampers compound of shear plates and round HSS sections - Ghamari, Ali; Seong-Hoon, Jeong; Thongchom, Chanachai; Putra Jaya, Ramadhansyah (Elsevier Ltd, 2023)
Though concentrically braced frames pertain to high elastic stiffness and strength, their low ductility has been introduced as a no-desirable system in the high seismic risk zone. Utilizing passive energy dampers as a capable and economical idea, the shortcoming can be solved. Experimental and numerical studies on the pipe dampers confirmed their satiable performance in the case of ductility and dissipating energy capacity. But, it is suffered from low strength and stiffness. To overcome the shortcoming of these types of metallic dampers, in this paper, the strengthening of pipe damper with shear plates is proposed and investigated numerically and parametrically. Subsequently, the required equations (in good agreement with finite element results) were presented to design and predict the behavior o the damper. Results indicated that by reduction of the length to the height of the damper, the strength and stiffness are improved. Also, the ratio of the strength of the flanges to the strength of the web affects the behavior of the damper, and increasing this ratio reduces the stiffness and ultimate strength. Therefore, it is suggested that this ratio should be greater than 1.5.